Twiddler's syndrome in patient with single chamber pacemaker (Faculty of Medicine Universitas Indonesia, 2011)
Twiddler's syndrome is a well-known complication of pacemaker treatment. This syndrome is characterized by coiling of the pacemaker lead due to the rotation of pacemaker generator on its long axis. Lead damage could cause lead facture or insulation leakage. The syndrome is also responsible for lead dislodgment, diaphragmatic stimulation, twitching upper arm due to plexus brachial nerve stimulation and loss of capture. Understanding risk factors and preventive measurement is very important. In this case report we present an 84 year-old patient who managed to rotate his single chamber pacemaker generator unintentionally following implantation in which the syndrome occurred within 2 months causing insulation leakage and battery depletion. For the best of our knowledge, this is the first report of twiddler's syndrome in Indonesia. (Med J Indones 2011;20:295-7)